A study on mandrel role in rotary draw bending of rectangular tube. (1st January 2015) - Liu, Kuanxin; Liu, Yuli; Yang, He
The mandrel die with cores is a significant factor affecting the forming quality of rectangular tube in rotary draw bending process. A new mandrel die is designed and manufactured, and the analytical formulas for the geometric parameters are deduced quickly and reasonably. 3D elastic–plastic FE model for the rotary draw bending process of rectangular tube employing the new mandrel die is established using ABAQUS. The model is validated to be credible and efficient by comparison with experiments, and the effects of mandrel die on the forming quality are investigated. It is shown that with the increase of core radius, core number and space length between adjacent cores, the thinning ratio increases, while the cross–section distortion ratio decreases. The larger mandrel extension induces larger thinning ratio and cross–section distortion ratio. When the core radius is large, the thickening ratio is small. Therefore, for the rectangular tube with dimensions 24.86 × 12.2 × 1 mm, the core radius 5 mm, extension length 0, space length 10 mm and core number 4 are selected to bend the rectangular tube with minor cross–section distortion and thickness changing ratio.